Interior Architecture as an agent of wellbeing - Smith, Dianne; Lommerse, Marina; Metcalfe, Priya (Journal of the Home Economics Institute of Australia, 2012)
Wellbeing is affected by our physical surroundings, which are an extension of who we are as people. The built environment, sensitively designed, can offer a sense of belonging for the individual, the family and the community, thereby positively affecting wellbeing. Interior architects can respond to the diverse needs and aspirations of people through their skills in design and their knowledge of occupation. This paper explores the attributes that interior architects bring to the perception and development of the built environment, and how they can contribute to wellbeing through their impact on social sustainability. It examines how socially sensitive and responsible interior architects can create environments that enrich people’s lives by redefining traditional constructs of interior architecture practice, and using interdisciplinary strategies to address issues of social sustainability in an increasingly complex world. Through real-life examples, the authors describe how interior architects can work to create built environments that are socially sustainable and responsible, and enhance the quality of life for individuals and communities. As a result, other disciplines may see opportunities for collaborative interdisciplinary work in the area of wellbeing.